(untitled) (Economic and Political Thought, 2016)
Social security of a subject as an individual is not discussed in literature in the way that makes it possible to categorise concepts and identify the achieved state of development and, as a result, use them in public policies. The concept of security presented in the report has been placed on the map of social security and, with respect to scientific disciplines, is a matter of political studies, social studies, economics and sociology. Such a broad methodological placement results from the adopted catalogue of indicators and discussed issues. The leitmotif of the analysis is determined by the relation between an individual and goods that are recognised as fundamental for the functioning of the society and meeting the needs of a man, an employee and a family. The research findings let the author verify the assumptions with regard to the epistemological component as well as social reality. However, he sees the need to develop a social perspective within the studies of security and, in the practical dimension, the whole range of dependence of the social and economic development determining individual social security.